Rancangan Sistem Pendaftaran Siswa Baru di SMA Pesat Bogor Berbasis Aplikasi Mobile Menggunakan React Native - All Matsani, Rinrin Milawati; Faizah, NM; Riyanto, Arif (Yayasan Kawanad, 2023)
SMA Pesat Bogor, a private high school in Bogor, attracts a lot of interest from prospective students. Even though it already has a website that provides information about various school activities and the online registration process for new students, the current registration system is considered complicated. Prospective students and their parents must navigate through various menus to access the registration form. In addition, the registration form currently used still uses Google Form, causing potential errors in data management because data can only be exported in .csv format. To overcome these problems, this research aims to design a mobile application-based new student registration application. This application will be developed using the PHP programming language, using the React Native framework, and using MySQL as a database to store registration information and user data. The limitations of this research include the use of mobile applications only for the registration process and checking registration results by parents of prospective students at SMA Pesat Bogor. The main objective of this research is to build a new mobile application-based student registration system for SMA Pesat Bogor. With the implementation of this application, it is hoped that it will make it easier for parents of prospective students in carrying out the registration process for SMA Pesat and simplify the tasks of officers responsible for registration activities by providing efficient data recording